ECTHR_COMMITTEE 3922/19 vom 5. Mai 2026 , AFFAIRE ARAVANTINOS c. GRÈCE - Ecthr Committee (2026)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure civile;Article 6-1 - Accès à un tribunal); Violation: 6;6-1